ANALISIS BENTUK KERUSAKAN DAN UPAYA PENANGANANNYA BENTENG BONE-BONE DI DESA BONE KECAMATAN BATUKARA - Burhan Alwi; Salniwati Salniwati; Akhmad Marhadi (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to identify the forms of damage and efforts to address the damage found at the Bone-Bone Fort, located in the Batukara District of Muna Regency. This research is a qualitative descriptive study supported by inductive reasoning. The data analysis used to address the formulation of problems in this research includes damage analysis and conservation analysis. In addition to data analysis, conceptual frameworks were also utilized to address the problem formulation, including the concepts of damage, weathering, vandalism, and conservation. Based on the research findings, the forms of damage identified at the Bone-Bone Fort consist of four types: (1) mechanical damage, characterized by the collapse of sections of the fort’s walls; (2) physical weathering, evidenced by cavities and holes in the stone material layers; (3) biological weathering, caused by tree root growth damaging the fort's walls; and (4) vandalism, including the theft of tombstones and damage to grave terraces. The efforts to address the damage to the fort include cleaning, restoration or repair, installation of perimeter fencing, environmental arrangement, and the establishment and reinforcement of legal protection.